Evaluation of Economic Education Related to Students' Thinking, Implementation and Knowledge Abilities at University - Rachmawati, Sela; Hudha, Choirul; Mardiyana, Lisana Oktavisanti (Future Science, 2023)
Developments and changes in the world of higher education are aimed at shaping and building quality human resource resilience now and in the future come. Evaluation Theory is an effort to achieve a form of higher education that is quality and superior. The aim is to find an overview related to the evaluation of students' thinking, implementation and knowledge abilities in higher education. Qualitative method through the observation process. Interviews and documentation. Focus: 1. How to Evaluate Students' Thinking Abilities in the field of economics; 2. How Evaluation of students' ability to carry out investigations in the field of economics; 3.How to Evaluate Students' Understanding Development Capabilities in a field economy. The research results show that students' thinking abilities need to be better developed with the HOT approach, Evaluation of Student Implementation Capabilities aims to create a forum for development and development that takes place in society. For evaluating knowledge capabilities in a process requires development a broad understanding of literacy with a more deeply convergent scientific basic build economic understanding in its development and development. Conclusion What is at the root of the value of this study is the evaluation of thinking abilities and skills implementation and development of understanding or literacy and knowledge are key success in building quality graduates, quality learning and higher education superior height.